Biodegradable polyurethanes from sugar cane biowastes - Jose-Roberto, Vega-Baudrit (2011)
In a previous work, it was demonstrated that 70% of the molasses isolated from the biowaste generated by the agro-industrialization of sugar cane allow obtaining composite materials with adequate mechanical properties and bulk density. In the present research, these results were applied in the preparation of composite polyurethanes based on sugar cane molasses reinforced with bagasse fiber from the same biowaste. Initially, milled fibers from bagasse were characterized both physically and chemically, according to their content of α-cellulose, moisture, ashes, hemicelluloses and lignin, as well as to their extractability in organic and aqueous solvents. The most representative values were α-cellulose (47.3%), lignin (24.4%) and holocellulose (66.1%). Subsequently, polyurethane foams (PUF) were prepared using the natural fiber as a reinforcement, with 4 different percentages of fiber ground (5, 10, 15, 20% w/w) with an average particle size of 60 mesh; an extra PUF without fiber reinforcement was also synthesized as a reference. PUF synthesis was carried out with a PEG-molasses mixture in a 30:70% (w/w) ratio, diphenylmethane diisocyanate (MDI) and dibutyltin dilaurate as catalysts. Composite PUFs were characterized according to their bulk density, thermal (thermogravimetry-TGA) and mechanical (compression modulus) properties. The results showed that the composite PUF sample with 10% sugar cane fiber added as reinforcement had the lowest bulk density. Also, its TGA thermal analysis showed a general trend towards reducing both the initial temperature of decomposition, as well as the temperature at the maximum rate of degradation, compared to the reference PUF without fiber added. Finally, its mechanical properties showed a maximum value for both effort to compression and compression modulus. It has been concluded that the use of agro-industrial biowaste from sugar cane permits to develop composite materials with suitable properties for applications as foams. The PUF synthesized by partial replacement of PEG for molasses and reinforced with sugar cane bagasse fiber can be used in the packaging industry. In this case, the materials are used for short periods, and are usually very bulky, less dense. Thus, this novel type of PU foam could be useful in reducing the production costs and in improving the potential biodegradability of the polymeric matrix, becoming an interesting value-added application for this important source of agricultural biowastes, especially in Latin America.